Rollover scheme for collegiate combined event athletes: a system for continuing training during academic breaks - Wilbourn, S. (Techniques Magazine, 2020)
Every college coach, at every division, knows what it is like to send their student-athletes home for winter break. You just had a great few months of fall training, and now they are going away for three to four weeks to train on their own! You hope and pray they will follow the plan you send home with them and will return after the holiday season healthy with work capacity in place, prepared to compete one week after the break ends! To make programming even more difficult, atheletes are traveling home, where the majority will have different training facilities and weather conditions. Add in holiday travel to Grandma's house and you have a recipe for disaster. In order to combat the interruptions to the training cycle, I have been utilizing a "rollover" scheme for my combined event athletes.